Allowable deviation of LC layer thickness in cholesteric LCDs - Rybalochka, A.; Sorokin, V.; Sorokin, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
The deviation of liquid crystal (LC) layer thickness in a display cell has considerable influence on the image quality at the addressing of cholesteric liquid crystal displays (ChLCD) by different kind of dynamic drive schemes. The driving principles that are realized in dynamic drive schemes by sequences of voltage pulses apply certain limitations on the value of this deviation. In this paper, we have compared allowable relative deviation of the LC layer thickness for two simple two-level dynamic drive schemes in ChLCD by the “dynamic hysteresis” method.